News stories framed episodically offer more diversified portrayals of immigrants. (June 2019) - Somaini, Francesco
This study investigated the representations of immigrants emerging from frames used in news stories in the two largest-circulation daily newspapers in Arizona: The Arizona Republic and the Arizona Daily Star. A quantitative content analysis of 380 stories published in the two dailies' websites in 2013 found the news coverage of immigration generally unfavorable to immigrants. Stories framed episodically provided less negative representations of immigrants than stories framed thematically did. Journalists interested in producing more diversified coverage of immigration should consider writing more stories using a predominantly episodic frame.